MODERN APPROACHES IN CLINICAL-ANAMNESTIC AND IMMUNOHISTOCHEMICAL ANALYSIS IN WOMEN WITH HYDATIDIFORM MOLE - Madrimova, K.K.; Matrizaeva, G.D.; Nishonov, D.A. (JOURNAL OF EDUCATION AND SCIENTIFIC MEDICINE, 2025)
Modern advances in the field of cell biology and the development of modern diagnostic methods have led to improved results of treatment of gynecological diseases and increased opportunities for preserving fertility in women. In particular, some forms of gestational trophoblastic disease, such as hydatidiform mole, detected early in pregnancy, have a favorable prognosis.